Penerapan Hukum Ekonomi Islam: Studi pada Zaman Rasulullah SAW dan Penerapannya di Indonesia. - Muhamad Musta’in (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
. The implementation of Islamic economic law in Indonesia remains informal and limited, unlike its comprehensive and integrated application during the era of Prophet Muhammad (PBUH). This study aims to examine the historical implementation of Islamic economic law during the Prophet’s time and compare it with its contemporary application in Indonesia. This research adopts a qualitative-descriptive approach using historical and normative literature studies. The findings indicate that Islamic economic principles such as distributive justice, prohibition of usury (riba), and social responsibility were practically enforced by the Prophet through public financial policies and market supervision. In Indonesia, despite the existence of institutions such as BMT, Islamic Financial Institutions (LKS), and the Compilation of Islamic Economic Law (KHES), implementation faces regulatory challenges and limited integration into the national legal system. This study recommends the need for harmonization between Islamic and national legal systems and emphasizes the importance of public literacy in Islamic economics.